Association between perfluoroalkyl and polyfluoroalkyl internal exposure and serum α-Klotho levels in middle-old aged participants - Min Li; Min Li; Yuanlin Ma; Wenli Cheng; Luyun Zhang; Cheng Zhou; Wenji Zhang; Wenjuan Zhang (Frontiers Media S.A., 2023)
PurposeExposure to perfluoroalkyl and polyfluoroalkyl substances causes oxidative stress, which is strongly associated with adverse health effects. Klotho protein plays an anti-aging role via antioxidation activity.MethodsWe investigated the levels of serum α-Klotho and PFAS exposure in adults who participated in the National Health and Nutrition Examination Survey from 2013 to 2016. A nationally representative subsample of 1,499 adults aged 40-79 years was analyzed for the associations of serum α-Klotho levels with serum PFAS exposures by correlation analysis and multiple general linear models. Of note, the potential confounding factors including age and gender were adjusted. Quantile-based g-computation models were used to assess the effects of mixed PFAS exposure on serum α-Klotho levels.ResultsThe weighted geometric mean of serum α-Klotho was 791.38 pg/mL for the subjects during 2013-2016. After adjusting for potential confounders, serum Klotho levels showed a statistically significant downward trend with increasing quartiles of PFOA and PFNA. Multivariate adjusted general linear regression analysis showed that increased exposure to PFNA was substantially associated with lower serum levels of α-Klotho, and each 1-unit increase in PFNA concentration was accompanied by a 20.23 pg/mL decrease in α-Klotho level; while no significant association was observed between other PFAS exposures and serum α-Klotho levels. It was negatively correlated between α-Klotho and Q4 for PFNA relative to the lowest quartile (Q1) of exposure (P = 0.025). It was found that the strongest negative correlation between PFNA exposure and serum α-Klotho levels was in the middle-aged (40-59 years) female participants. Furthermore, the mixture of the four PFAS substances showed an overall inverse association with serum α-Klotho concentrations, with PFNA being the major contributor.ConclusionsTaken together, in a representative sample of the U.S. middle-aged and elderly populations, serum concentrations of PFAS, especially PFNA, have been negatively associated with serum levels of α-Klotho, which is strongly associated with cognition and aging. It was important to note that the majority of associations were limited to middle-aged women. It will be meaningful to clarify the causal relationship and the pathogenic mechanisms of PFAS exposure and α-Klotho levels, which is helpful to aging and aging-related diseases.